2019
DOI: 10.1021/acs.jced.9b00981
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria in the Aqueous Quinary System Na+, Mg2+//Cl, NO3, SO42––H2O and Its Subsystem at 258 K

Abstract: The experimental study on phase equilibria at 258 K in the quinary system Na+, Mg2+//Cl–, NO3 –, SO4 2––H2O and its subsystem Na+, Mg2+//Cl–, NO3 ––H2O were investigated using the isothermal solution equilibrium method. The phase diagrams were obtained on the basis of the measured data. The investigated systems belong to simple cosaturated types without double salts formed. The quinary system saturated with NaCl·2H2O contains three isothermal-invariant points, seven univariant curves, and five crystallization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The adsorption capacity increased with the increase of temperature, indicating an endothermic process and the adsorption process was dominated by chemical adsorption. 30 PS-SBT and CHA-111 displayed striking difference in adsorption performance at 293 K, 303 K and 313 K. The adsorption performance of CHA-111 decreased with the increase of temperature, indicating that high temperature was not conducive to adsorption of 1,3-propanediol 40 and it was an exothermic process (the isothermal model of CHA-111 was shown in Fig. 8B).…”
Section: Inuence Factors Of Adsorptionmentioning
confidence: 98%
See 1 more Smart Citation
“…The adsorption capacity increased with the increase of temperature, indicating an endothermic process and the adsorption process was dominated by chemical adsorption. 30 PS-SBT and CHA-111 displayed striking difference in adsorption performance at 293 K, 303 K and 313 K. The adsorption performance of CHA-111 decreased with the increase of temperature, indicating that high temperature was not conducive to adsorption of 1,3-propanediol 40 and it was an exothermic process (the isothermal model of CHA-111 was shown in Fig. 8B).…”
Section: Inuence Factors Of Adsorptionmentioning
confidence: 98%
“…18 Hyper-crosslinked resin as a physical regulated resin owns high specic surface area and rich pore diameter structure, which has been widely used in the adsorption and separation of phenols, 19,20 anilines, [21][22][23] dyes 24 and other substances. Besides, the introduction of chemical functional groups on resin skeleton can improve the surface properties of resins, exhibiting good adsorption and separation performance for phenols, [25][26][27] amines [28][29][30] and other substances. However, there are few reports on the selective adsorption of polyols by adjusting the physical or chemical structure of resin.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the existing literature mainly focuses on nitrate and sulfate salt solubility. For example, Huang studied liquid–solid equilibrium of the Na + , K + , Mg 2+ //Cl – , NO 3 – , SO 4 2– –H 2 O system and part of its subsystems at 258.15 K and 298.15 K; Zhou studied the effect on the potassium salt yield and product quality of carnallite processing by magnesium sulfate; Gong measured the Na + , Mg 2+ //Cl – , SO 4 2– –H 2 O system; and Jin studied the phase equilibrium of the Na + , K + , Mg 2+ //Cl – , SO 4 2– –H 2 O quinary system at 288 K. In addition, regarding K-carnallite systems, phase equilibrium studies are mainly focused above room temperature, with few low-temperature studies. Tursunbadalov , constructed a total phase equilibria diagram for the Na, K, Mg//Cl, SO 4 –H 2 O seawater system at 0 and 25 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies by our research group revealed that the liquid phase composition and the solid phase composition of brine will change significantly when the temperature drops to 258.15 K compared to the normal temperature, many double salts no longer precipitate or their crystallization zones decrease in phase diagrams at low temperatures (258.15 K), simplifying the phase equilibrium relationship, facilitating lithium enrichment and streamlining production technology. Consequently, it is crucial to investigate the phase equilibrium of complex systems at low temperatures.…”
Section: Introductionmentioning
confidence: 99%